Dependence of Ga-doped ZnO thin film properties on different sputtering process parameters: Substrate temperature, sputtering pressure and bias voltage - Castro, M. V. (2015)
This paper reports on the effects of different sputtering deposition process parameters (substrate temperature, sputtering pressure and bias voltage) on the electrical, optical, structural and morphological properties of gallium-doped ZnO (ZnO:Ga) of ~1 μm thick. These highly transparent and conductive films were deposited on glass surfaces by d.c. pulsed magnetron sputtering from a GZO (ZnO(95.5):Ga2O3(4.5)) ceramic target in an argon atmosphere. X-ray diffraction experiments show that all films have a hexagonal wurtzite structure with the [001] preferred crystallographic direction, and themorphology of the films (obtained fromscanning electron microscope analysis) is sensitive to the process parameters. All ZnO:Ga films have an average transmittance above 80% in the visible region, and the lowest electrical resistivity of 3.03 × 10−4 Ω·cm was achieved for the sample submitted to the lowest bias voltage (−40 V), which corresponds to a carrier concentration and a carrier mobility of 6.99 × 1020 cm−3 and 29.49 cm2 V−1 s−1, respectively. A high substrate temperature, high sputtering pressure and lownegative bias voltage (within the range of studied parameters) proved to be very promising on obtaining optimized ZnO:Ga films, ensuring suitable properties for application as transparent electrodes in photovoltaic cells.